Synthesis of highly sinterable Tm, Ho:(Lu1-xScx)2O3 powders by spray co-precipitation for transparent ceramics: Influence of the variable x. Issue 9 (1st May 2021) - Yang, Hanlin; Xu, Tao; Li, Fang; Yu, Shengquan; Kang, Bin; Liu, Xin; Wang, Yaozhi; Liu, Jiachen; Jing, Wei
Abstract: Highly sinterable Tm, Ho:(Lu1- x Sc x )2 O3 nanopowders were synthesized by a spray co-precipitation method. The influences of the calcination temperatures and x values on the morphology and composition of the powders were studied. The results indicated that the precursor gradually formed needlelike structures with increasing x values, and the powders calcined at 1100 °C for 2 h exhibited the highest uniformity and sintering activity. Using the powders calcined at 1100 °C, the Tm, Ho:(Lu1- x Sc x )2 O3 ceramics with the highest in-line transmittance of 79.80% at 2090 nm were fabricated by vacuum sintering at 1550 °C for 10 h and further hot isostatic pressing under 190 MPa at 1700 °C. Owing to the disordered crystal structure of the (Lu1- x Sc x )2 O3, the grain size of the ceramics decreased from 1.72 ìm to 1.16 ìm, and the emission spectra showed some variation with increasing x values. This work demonstrates promise in facilitating the production of Tm, Ho:(Lu1- x Sc x )2 O3 transparent ceramics for their use in 2 ìm ultrashort laser pulse and other applications.